The Influence of Initiative Signature‐Gathering Campaigns on Political Participation1. (11th July 2013) - Boehmke, Frederick J.; Alvarez, R. Michael
<x xml:space="preserve">Abstract</x> Objective This article studies the effect of initiative signature‐gathering campaigns on political participation within a state. Methods Using data on signatures gathered for eight initiatives and four different elections, we conduct grouped logit regression to test whether counties that are subject to more intense signature‐gathering campaigns, measured by the number of signatures gathered per capita, experience greater levels of turnout and ballot roll‐off in the subsequent election. Results Our analysis provides evidence that the intensity of signature‐gathering campaigns has a moderate effect on both of these measures of political participation. Conclusion Initiative campaigns influence turnout not just at the state level, but variation in campaigns leads to differences within states as well.